Monitoring of carbon monoxide (CO) with sentinel-5P satellite images for the province of Huanuco (LACCEI, 2024)
One of the biggest environmental problems in recent years in our country is the emission of carbon monoxide from the air by burning brush or garbage, emissions from industry, an old vehicle fleet, etc. The emission of this gas in large quantities is a considerable variable for climate change and when it is breathed by people it generates serious health problems. Currently this is happening in some districts of the province of Huanuco. For this reason, and given the lack of air quality monitoring stations in the area, it was proposed to carry out an investigation that would allow us to determine the amounts of carbon monoxide on a temporal and spatial scale for each district of the studied province, during and after the COVID 19 pandemic, between the years 2019 and 2022, to find out if this event in any way caused an effect on the emissions of this gas.